Mini-plus percutaneous setting in total laparoscopic hysterectomy. Issue 2 (1st February 2022) - Misirlioglu, Selim; Giray, Burak; Vatansever, Dogan; Arslan, Tonguc; Urman, Bulent; Taskiran, Cagatay
Abstract: Introduction: We aimed to analyze the preliminary experience of a mini-plus percutaneous instrument (MpPc) setting in total laparoscopic hysterectomy (TLH). Material and methods: Forty-three women who underwent a mini-plus percutaneous total laparoscopic hysterectomy at a tertiary-care university-based teaching hospital and academic affiliated private hospital between May 2017 and 2018 were included. MpPc-TLH was performed through one optical trans-umbilical 5-mm trocar, one 5-mm ancillary port on the right side, either one 2.4-mm percutaneous endoscopic instrument or 3-mm mini-laparoscopic port on the right upper quadrant and if required one 3-mm ancillary port on the left lower quadrant. Results: A total of 43 patients were included, with a median age of 48 years (range, 38–71 years). Indication for surgery included uterine myomas ( n  = 20), benign adnexal mass ( n  = 7), endometrial intraepithelial neoplasia ( n  = 6), endometrial cancer ( n  = 5), adenomyosis with abnormal bleeding ( n  = 3), and high-grade cervical dysplasia ( n  = 2). The median operating time was 100 min (range, 60–180 min), and the median estimated blood loss was 30 ml (range, 20-60ml). The median postoperative abdominal pain Visual Analog Scale score was 3 (range, 0-6). Conclusions: The preliminary data suggest that MpPc approach is a feasible and safe surgical modality for total laparoscopic hysterectomy.